Water loss performance indicators in peripheral areas of a metropolitan region in Amazonia - Araújo Junior, Antônio Jorge Silva; Viegas, Alessandro Abadessa; Fernandes, Lindemberg Lima; Teixeira, Luiza Carla Girard Mendes (Electronic Journal "Fórum Ambiental da Alta Paulista", 2022)
This paper aims to quantify and compare the losses of two isolated water supply systems with similar characteristics (Canarinho e Benjamin Sodré), located in the Metropolitan Region of Belém, state of Pará, Amazonia-Brazil. The methods included diagnosis of systems, technical documental and commercial surveys from the water supply utility, outflow measurements (ultrasound portable outflow measurer and pitometer type equipment with transductor and data logger), statistical treatment of data and determination of the loss indexes of the water supply systems. The high Distribution Network Loss Index recorded of Canarinho and Benjamin Sodré with 81.98% and 70.04% respectively, jointly observed with Connection Losses Index values ​(3.2 and 7.3 times higher, respectively, compared to the national average) increased the Water Meter Index of the studied systems (Canarinho with 84.66% and Benjamin Sodré with 70.93%). The high water loss rates are a characteristic of the northern region of Brazil and are reflected in the data obtained from the studied systems. Losses of this magnitude make systems economically unsustainable due to frauds, lack of maintenece and a poor quality or degradation of infrastructure.